Genome-Wide Scan for Parent-of-Origin Effects in a sub-Saharan African Cohort With Nonsyndromic Cleft Lip and/or Cleft Palate (CL/P). (July 2022) - Gowans, Lord J. J.; Comnick, Carissa L.; Mossey, Peter A.; Eshete, Mekonen A.; Adeyemo, Wasiu L.; Naicker, Thirona; Awotoye, Waheed A.; Petrin, Aline; Adeleke, Chinyere; Donkor, Peter; Busch, Tamara D.; James, Olutayo; et al.
Objective: Nonsyndromic cleft lip and/or cleft palate (NSCL/P) have multifactorial etiology where genetic factors, gene–environment interactions, stochastic factors, gene–gene interactions, and parent-of-origin effects (POEs) play cardinal roles. POEs arise when the parental origin of alleles differentially impacts the phenotype of the offspring. The aim of this study was to identify POEs that can increase risk for NSCL/P in humans using a genome-wide dataset. Methods: The samples (174 case-parent trios from Ghana, Ethiopia, and Nigeria) included in this study were from the African only genome wide association studies (GWAS) that was published in 2019. Genotyping of individual DNA using over 2 million multiethnic and African ancestry-specific single-nucleotide polymorphisms from the Illumina Multi-Ethnic Genotyping Array v2 15070954 A2 (genome build GRCh37/hg19) was done at the Center for Inherited Diseases Research. After quality control checks, PLINK was employed to carry out POE analysis employing the pooled subphenotypes of NSCL/P. Results: We observed possible hints of POEs at a cluster of genes at a 1 mega base pair window at the major histocompatibility complex class 1 locus on chromosome 6, as well as at other loci encompassing candidate genes such as ASB18, ANKEF1, AGAP1, GABRD, HHAT, CCT7, DNMT3A, EPHA7, FOXO3, lncRNAs, microRNA, antisense RNAs, ZNRD1, ZFAT, and ZBTB16 . Conclusion: Findings from our study suggest that some loci may increase the risk for NSCL/P through POEs. Additional studies are required to confirm these suggestive loci in NSCL/P etiology.